Three new compounds from the flower branch of Gastrodia elata Blume and anti-microbial activity. Issue 25 (13th April 2020) - Yang, Liu; Jiang, Rong; Li, Hui-Hui; Pan, Ya-Ping; Lu, Jing-Jin; Zhang, Hong; Liu, Shou-Jin; Shen, Ji-Lu; Hu, Jiang-Miao
Abstract : Three new compounds (1–3 ): gastrodinol (1 ), 2-(4′-hydroxybenzoyl)-3-hydroxyethyl indole (2 ) and 2-(4′-hydroxybenzoyl)-3-(4′′-hydroxybenzyl)indole (3 ) were isolated from the flower branch of G. elata, and anti-microbial activity. Abstract : Three new compounds (1–3 ), including novel tetra- p -cresol substituted cyclopenta[ a ]naphthalene derivatives, named gastrodinol (1 ), 2-(4′-hydroxybenzoyl)-3-hydroxyethyl indole (2 ), 2-(4′-hydroxybenzoyl)-3-(4′′-hydroxybenzyl)indole (3 ) were isolated from the flower branch of G. elata, along with five known compounds (4–8 ). Among them, compound 1 exhibited the most anti-microbial activity against Streptococcus agalactiae, with the minimum inhibitory concentration of 1 μg ml −1 . This study demonstrated that the novel gastrodinol 1 found in the flower branch of G. elata may be responsible for the anti-microbial effect. It will lead to the development of new antibiotics, and how to utilize the TCM ′′Tianma′′ better.